The TRANZAC and Social Problems re: COVID 19 and Performing Musicians - Wiseman, Bob (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Exploring COVID-19 through the TRANZAC, a Toronto performance hub. This piece is in the form of a zine.